(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2026)
This article draws on a passage from the work of a team of teacher trainers in the City of Buenos Aires who propose teaching the subject matter beyond the classroom, through visits to museums and memorial sites. These educational outings are part of a training process that democratizes access to cultural assets, promotes active memory, and strengthens the formation of critical individuals committed to democratic values. In this case, we present a visit sheet prepared in 2023 for second-cycle teachers—particularly those teaching 7th grade—to learn about the Parque de la Memoria / Monument to the Victims of State Terrorism. This proposal has taken on new meaning in the face of denialist narratives that deny, relativize, or justify state terrorism, and in the face of anti-scientific discourses. In this context, sites of memory are strategic spaces for teaching recent history and addressing collective memory.